Safety profile and impact of low-titer group O whole blood for emergency use in trauma. Issue 1 (January 2020) - Williams, James; Merutka, Nicholas; Meyer, David; Bai, Yu; Prater, Samuel; Cabrera, Rodolfo; Holcomb, John B.; Wade, Charles E.; Love, Joseph D.; Cotton, Bryan A.
Abstract : PURPOSE: Following US military implementation of a cold-stored whole blood program, several US trauma centers have begun incorporating uncrossmatched, group O cold-stored whole blood into civilian trauma resuscitation. We set out to evaluate the safety profile, transfusion reactions events, and impact of low-titer group O whole blood (LTO-WB) at our center. METHODS: In November 2017, we added LTO-WB to each of our helicopters and to our emergency department (ED) refrigerator, alongside that of existing red blood cells and plasma. We collected information on all patients with trauma receiving prehospital or ED transfusion of uncrossed, emergency release blood products between November 2017 and June 2018. Patients were divided into those receiving any LTO-WB and those receiving only red blood cell and or plasma (COMP). Serial hemolysis panels were obtained at 3 hours, 24 hours, and 48 hours. All data were run using STATA 12.1. Statistical significance was set at p < 0.05. RESULTS: One hundred ninety-eight patients received LTO-WB and 152 patients received COMP. There were no differences in age, sex, or mechanism. The LTO-WB patients had higher chest Abbreviated Injury Scale scores (median, 3 vs. 2; p = 0.027), as well as worse arrival base excess (median, −7 vs. −5; p = 0.014) and lactate (5.1 vs. 3.5; p < 0.001). The LTO-WB patients received less post-ED blood products than the COMP patients (median, 0 vs. 3; p = 0.001). There was no difference in survival (LTO-WB, 73%; COMP, 74%; p = 0.805). There were only two suspected transfusion reactions, both in the COMP group ( p = 0.061). There was no difference in hemolysis panel values. Controlling for age, severity of injury, and prehospital physiology, LTO-WB was associated with a 53% reduction in post-ED blood product transfusion (odds ratio, 0.47; 0.23–0.94 95% CI; p = 0.033) and two-fold increase in likelihood of survival (odds ratio, 2.19; 1.01–4.76 95% CI; p = 0.047). CONCLUSION: Low-titer group O whole blood has similar evidence of laboratory hemolysis, similar transfusion reaction rates, and is associated with a reduction in post-ED transfusions and increase likelihood of survival. LEVEL OF EVIDENCE: Therapeutic, Level II.